THE STUDY OF INDIVIDUAL LACTATION CURVES OF TWO IRANIAN BUFFALO ECOTYPES - Kianzad, Davood; Seyyedalian, Seyyed Ahmad Reza; Hasanpur, Karim; Javanmard, Arash (Proceeding Buffalo International Conference, 2013)
The aims of the current study were to study the effects of some environmental factors such as year of birth, year of calving, age at calving, parity, season of calving, and village on lactation curve traits (initial milk yield, peak yield, days to attain peak yield, inclining and declining slope of lactation, persistency, and 240-d milk yield) and to estimate phenotypic correlations among the traits in Khuzestani and Azeri buffalo ecotypes. The used dataset consisted of 15,396 and 9,283 lactations from 6,632 and 3,558 Khuzestani and Azeri buffaloes, respectively, which were collected from 1992 to 2009 by the Animal Breeding Center of Iran. The results showed that factors such as age at calving, season of calving, parity, village, year of birth, and year of calving had significant effects (P<0.05) on the majority of the lactation curve traits. The highest declining slope but the lowest peak yield and 240-d milk yield were for buffaloes with age greater than 132 months. Initial milk yield, peak yield and 240-d milk yield were the lowest for the 1st parity buffaloes and increased with the number of parity. The season of calving affected Khuzestani ecotype significantly (P<0.05), so that lower peak yield and drop of milk yield with higher rate after peak (P<0.05) caused lower 240-d milk yield (P<0.05) for those calving out of season in Khuzestani ecotype, whereas this event was not observed in Azeri ecotype. The results showed that non-genetic factors play an important role in determining both milking pattern and total performance of lactating buffaloes.